Employment and capital formation in underdeveloped economies - Bhatt, Vinayak Vijayshanker (Bombay : Orient Longmans, 1960)
The book has the following chapters: Underemployment in Underdeveloped Economies: Theoretical Considerations; Capital-Output Ratios of Certain Industries: A Comparative Study of Certain Countries; Capital Intensity of Industries: A Comparative Study of Certain Countries; Employment and Capital Formation; Choice of Techniques: Empirical Possibilities; and Motor Force of Economic Development.
Includes bibliographical references and index.
rpm 30/10/2017
Loans
Keywords: Economic development; Capital; Unemployed; Developing countries